Experimental Study on The Application of Taguchi Design of Experiment (DoE) and ANOVA for a Waste-Based Composite Material - Didik Sugiono; Anik Rufaidah; Miftahul Ulum; Rohmat Rohmat (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
The increasing amount of industrial and agricultural waste necessitates innovation in the use of environmentally friendly alternative materials in the construction sector. This research aims to analyze the influence of varying cement, sand, seashell powder, and coconut fiber powder compositions on the compressive strength and porosity of paving blocks using the Taguchi method and ANOVA. The experimental design uses an orthogonal array L16 (4⁴), resulting in 16 experimental combinations. The test results indicate that coconut husk powder is the most significant factor influencing porosity, while other factors have a relatively small effect. The optimum parameters for porosity were obtained at a cement composition of 643.24 g, sand 915.84 g, seashell powder 686.883 g, and coconut fiber powder 0 g. Meanwhile, the optimum compressive strength was achieved at cement 643.23 g, sand 2289.60 g, seashell powder 228.961 g, and coconut fiber powder 0 g. Regression analysis showed that the model had a good fit with an R² of 0.8967 for porosity and 0.5625 for compressive strength. This research proves that utilizing clamshell and coconut husk waste has the potential to produce high-quality paving blocks while also supporting sustainable waste management.